2023
DOI: 10.1371/journal.pone.0282911
|View full text |Cite
|
Sign up to set email alerts
|

3D-printed eye model: Simulation of intraocular pressure

Abstract: Purpose To develop artificial eye models using 3D printing and to evaluate the correlation between different corneal thicknesses and intraocular pressures (IOPs). Methods We designed 7 artificial eye models using a computer-aided design system and fabricated them using 3D printing. Corneal curvature and axial length were based on the Gullstrand eye model. Hydrogels were injected into the vitreous cavity, and seven different corneal thicknesses (200 to 800 μm) were prepared. In this proposed design, we also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Eight eyes with different central corneal thicknesses were prepared to simulate different IOPs. With the 3D-printed eye model, we confirmed that corneal thickness was significantly correlated with IOP using a Tono-Pen AVIA tonometer (Reichert Inc., Depew, New York, USA) [ 11 ]. To simplify the simulation of the elevated IOP model, we generated artificial eye models without eyelids by changing the corneal thickness via 3D printing.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Eight eyes with different central corneal thicknesses were prepared to simulate different IOPs. With the 3D-printed eye model, we confirmed that corneal thickness was significantly correlated with IOP using a Tono-Pen AVIA tonometer (Reichert Inc., Depew, New York, USA) [ 11 ]. To simplify the simulation of the elevated IOP model, we generated artificial eye models without eyelids by changing the corneal thickness via 3D printing.…”
Section: Methodsmentioning
confidence: 77%
“…To verify the measurement of IOP using the TET, we generated an elevated IOP model with 3D printing technology [ 11 ]. Eight eyes with different central corneal thicknesses were prepared to simulate different IOPs.…”
Section: Methodsmentioning
confidence: 99%
“… 8 Moreover, in terms of manufacturing via 3D printing, different models of ideal eyeballs for the estimation of intraocular pressure were based on corneal thickness, and this technique could be a promising alternative to the conventional porcine eye model. 9 …”
Section: Introductionmentioning
confidence: 99%
“…The benefit of 3D printing is increased production speed, reproducibility, and ease of printing adjustments, which allow for mass production as well as customizability. Thus far, 3D printing has been utilized for multiple ophthalmic applications, including the production of model eyes for diagnostics [16], surgical education [17], surgical implants [18], surgical instrumentation and devices [19], and ocular prostheses [20,21]. Of particular interest is the report of the production of a realistic 3D printed ocular prosthesis by Groot et al in 2021.…”
Section: Introductionmentioning
confidence: 99%